2014
DOI: 10.1111/pde.12420
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerated Infantile Hemangioma: Novel Treatment with Topical Brimonidine‐Timolol

Abstract: We report a 2-month-old boy with a painful ulcerated hemangioma on the lower mucosal lip extending to the vermillion border that caused feeding difficulty. It was successfully treated with topical brimonidine 0.2% and timolol 0.5%, a combination selective α2 -adrenergic agonist and nonselective β-blocker. After 6 weeks of treatment, the lesion reepithelialized and the patient's symptoms and functional complications resolved. Brimonidine 0.2% timolol 0.5% ophthalmic solution is an emerging alternative treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
0
9
0
1
Order By: Relevance
“… 1 However, the reported cases of ulcerated IH treated with topical β-blocker had no recurrence at up to 18 months follow-up after therapy cessation, including our patient. Our patient appeared pain-free during timolol dressing changes, and Beal et al 21 found that their patient with ulcerated lip IH could feed well after brimonidine–timolol application, suggesting topical β-blockers minimize ulcer-pain like propranolol.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“… 1 However, the reported cases of ulcerated IH treated with topical β-blocker had no recurrence at up to 18 months follow-up after therapy cessation, including our patient. Our patient appeared pain-free during timolol dressing changes, and Beal et al 21 found that their patient with ulcerated lip IH could feed well after brimonidine–timolol application, suggesting topical β-blockers minimize ulcer-pain like propranolol.…”
Section: Discussionmentioning
confidence: 49%
“…To the best of our knowledge, there have been 8 reported cases of localized ulcerated IH successfully treated with topical β-blocker (Table 1 ). 4 , 5 , 18 21 Average age of these children at initiation of therapy was 2.3 months (range, 0.4–7 months). Dimensions of the widest ulceration ranged from 12 to 50 mm.…”
Section: Discussionmentioning
confidence: 99%
“…No ulcerated perioral hemangiomas were treated in our cohort and we caution against use of timolol in this area, despite reports of tolerability. 4 Our data suggest that timolol may be a well-tolerated alternative to oral propranolol in treating IH ulceration up to approximately 3 cm in size. However, we recommend a comprehensive history and physical examination and close clinical follow-up to monitor for potential adverse events of beta-blockade.…”
mentioning
confidence: 63%
“…Of the 1230 patients reviewed in our study, 613 were treated with systemic antibiotics, 200 with pulsed dye laser, 197 with oral propranolol, 54 with atenolol, 46 with topical timolol, 25 with pulsed dye laser and Nd:YAG laser, 12 with topical becaplermin, 12 with surgical resection, 8 with wound care alone, 5 with captopril, 1 with vincristine, 19 with combination therapies, and 38 with other, less common, treatment modalities (Table 2). 55 Boos and Castelo-Soccio 56 Cante et al 45 Chang and Kang 4 Neri et al 46 Thomas et al 28 Tlougan et al 57 Weibel et al 31 58 Bagazgoitia et al 59 Ben-Zvi and Gass 60 Bernabeu-Wittel et al 61 Betlloch-Mas et al 9 Bouras et al 62 Cavalli et al 13 Gidaris et al 63 Gulati and Jury 10 Hermans et al 64 Hong and Fischer 47 Kim et al 2 Lanoel et al 65 Morais et al 11 Mousa et al 14 Naouri et al 66 Nelson et al 67 Oksiuta et al 68 Pavlakovic et al 15 Saaiq et al 69 Sadykov et al 70 Saint-Jean et al 8 Sans et al 71 Sharma et al 72 Tan et al 12 Thomas et al 73 Tiwari et al 7 Vercellino et al 74 76 Hermosa et al 33 Lacour et al 36 Morelli et al 34 Ward et al 50 Bookout et al 41 Chang et al…”
Section: Discussionmentioning
confidence: 99%